2021
DOI: 10.1016/j.isci.2021.102723
|View full text |Cite
|
Sign up to set email alerts
|

Consensus driven by a minority in heterogenous groups of the cockroach Periplaneta americana

Abstract: Many social species are able to perform collective decisions and reach consensus. However, how the interplay between social interactions, the diversity of preferences among the group members and the group size affects these dynamics is usually overlooked. The collective choice between odourous and odorless shelters is tested for the following three groups of social cockroaches (Periplaneta americana) which are solitary foragers: naive (individuals preferring the odorous shelter), conditioned (individuals witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…This suggests that individual memory or interindividual behaviours (e.g. idiosyncrasy) [ 62 , 63 ] are negligible in our experiment. For the groups, the number of individuals in the RG shelter at the end of the trials and at 600 minutes are significantly correlated (Spearman test: ρ = 0.58, P = 0.005, Fig 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that individual memory or interindividual behaviours (e.g. idiosyncrasy) [ 62 , 63 ] are negligible in our experiment. For the groups, the number of individuals in the RG shelter at the end of the trials and at 600 minutes are significantly correlated (Spearman test: ρ = 0.58, P = 0.005, Fig 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the consequences of heterospecific aggregation on decision processes are mostly unknown [1,16,50]. Here, tiny variations in the balance of larval cues may have changed final aggregation outputs, leading to various unstable configurations [18,49,51,52]. Further, each individual larva may have slightly different life-history traits, physiological requirements [10,40] and even personality [47], resulting in different choices.…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that the accuracy of the group motion towards the direction known by the informed agents increases asymptotically as the proportion of informed individuals increases, and that the larger the group, the smaller the proportion of informed individuals needed to guide the group with a given accuracy. A recent study on cockroaches [3] has shown that a minority of individuals preferring one shelter over the other can influence the population to reach a consensus for only one site. The technique of using informed individuals to steer the collective dynamics has already been used in artificial systems with various types of collective behaviours.…”
Section: Introductionmentioning
confidence: 99%